Placental model as an important tool to study maternal-fetal interface - Gonçalves, Bianca M. [UNESP] (2022)
The placenta is a temporary organ that plays critical roles at the maternal-fetal interface. Normal development and function of the placenta is dependent on hormonal signaling pathways that make the placenta a target of endocrine disrupting chemical (EDC) action. Studies showing association between prenatal exposure, hormone disruption, and reproductive damage indicate that EDCs are developmentally toxic and can impact future generations. In this context, new placental models (trophoblast-derived cell lines, organotypic or 3D cell models, and physiologically based kinetic models) have been developed in order to create new approach methodology (NAM) to assess and even prevent such disastrous toxic harm in future generations. With the widespread discouragement of conducting animal studies, it has become irrefutable to develop in vitro models that can serve as a substitute for in vivo models. The goal of this review is to discuss the newest in vitro models to understand the maternal-fetal interface and predict placental development, physiology, and dysfunction generated by failures in molecular hormone control mechanisms, which, consequently, may change epigenetic programming to increase susceptibility to metabolic and other disorders in the offspring. We summarize the latest placental models for developmental toxicology studies, focusing mainly on three-dimensional (3D) culture models.